Work-related information-seeking behaviour of janitors at the University of Dar es Salaam, Tanzania - Mkhai, Emmanuel; Kassim, Mohamed (University of Dar es Salaam Library Journal, 2023)
The main purpose of this study was to investigate the information needs and seeking behaviour of janitors working at the University of Dar es Salaam. A descriptive research design with a mixed research approach was used to study the information-seeking behaviour of the janitors. Results revealed that the majority of respondents had a multitude of work-related information needs including financial, health and safety at the workplace, work contracts, workers ' rights, and ethical information. The results further revealed that the majority of the study respondents relied heavily on their friends, mobile phones, social media, and relatives to meet their different work-related information needs. Results showed that most respondents had inadequate information literacy skills that limit their ability to comprehend work-related information and identify relevant sources where they could search and obtain reliable work-related information. The findings of this study have practical implications for formulating strategies for providing work-related information to the underprivileged working class such as the janitors. Understanding the information-seeking behaviour of janitors is imperative to meaningfully responding to their information needs. A better understanding of the janitors ' work-related information needs, sources, and challenges they face when seeking such information will help to design an appropriate information delivery system that will consider the information-seeking behaviour of this underprivileged working class.